2015
DOI: 10.1111/cgf.12656
|View full text |Cite
|
Sign up to set email alerts
|

Map‐based Visualizations Increase Recall Accuracy of Data

Abstract: Figure 1: We investigate the memorability of relational data represented with node-link (left-side) and map-based (right-side) visualizations; shown are a node-link and a map-based visualization with 200 nodes and 500 links from the LastFM dataset. AbstractWe investigate the memorability of data represented in two different visualization designs. In contrast to recent studies that examine which types of visual information make visualizations memorable, we examine the effect of different visualizations on time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 38 publications
(71 reference statements)
0
37
0
Order By: Relevance
“…The tasks are grouped with respect to their type: group-only task (GOT), group-vertex task (GVT), group-edge task (GET) or group-network task (GNT) that adding contours does not negatively impact the performance of network-based tasks and the GMap approach outperforms colored nodes with respect to group-based tasks. In a second study, Saket et al [SSKB15] report on experiments measuring the extent to which people remember the data depicted in these two types of group structure visualizations. The 40 participants of the study had to do tasks-including one group-only task and one group-vertex task-four days after being exposed to the visual stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The tasks are grouped with respect to their type: group-only task (GOT), group-vertex task (GVT), group-edge task (GET) or group-network task (GNT) that adding contours does not negatively impact the performance of network-based tasks and the GMap approach outperforms colored nodes with respect to group-based tasks. In a second study, Saket et al [SSKB15] report on experiments measuring the extent to which people remember the data depicted in these two types of group structure visualizations. The 40 participants of the study had to do tasks-including one group-only task and one group-vertex task-four days after being exposed to the visual stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The space of experimental designs for visualization studies can be described along multiple dimensions, several of which we describe here: [50], while studies that measure participants' ability to memorize visual information for an extended period of time may involve multiple sessions conducted several days apart [88]. -Type of participants: Studies may involve naive participants, or participants with a particular expertise or ability.…”
Section: Types Of Experiments and Associated Methodologiesmentioning
confidence: 99%
“…Graph revisitation tasks and simple memorability tests can be performed in crowdsourced settings, although drawing tasks will likely be much more difficult. Saket et al [89] present evidence that different visual designs can significantly impact the recall accuracy of the data being visualized, specifically, comparing node-link visualizations to map-based visualizations. This was measured by asking participants to perform certain tasks with both types of visualizations and later on asking them again to perform a subset of the tasks without the visualization.…”
Section: Measures Beyond the Standardmentioning
confidence: 99%
“…Work by Skupin et al (2013) evaluated the utility and legibility of self-organizing maps for mapping and understanding the structure of science. Prior work on the general legibility of network versus map-based visualizations of data showed that map-based visualizations do increase recall accuracy of data (Saket et al 2014, 2015). Other work compared animations with static visualizations of temporal graph layouts (Farrugia and Quigley 2011).…”
Section: Prior Workmentioning
confidence: 99%